AB1054 Quantitative ultrasound for assessment of disease activity in patients with rheumatoid arthritis: reliability and construct validity. (15th June 2017) - Goswami, RP; Ghosh, A; Lahiri, D; Ghosh, P
Abstract : Background: Joint ultrasound is an integral part of assessment of patients with rheumatoid arthritis (RA). Semi-quantitative grading of ultrasound is subjective whereas quantitative ultrasound (QUS) may be more objective. Objectives: To evaluate the reliability and construct validity of QUS of wrist joints in patients with RA. Methods: We studied 95 patients with RA. Following parameters were studied: swollen and tender joint counts (SJC and TJC), patient and evaluator global assessment (PGA, EGA) and disease activity score (DAS28). Patients were classified as active disease and disease in remission as per expert clinician opinion. Colour Doppler ultrasound (CDUS) of wrists was done to obtain semiquantitative grading. Scans were processed in image analysis software (Photoshop CS4) to obtain the following: colour fraction of intrasynovial (IS) vascular signals (CF(IS) = pixel area of IS vascular signals/pixel area of entire IS area (area(IS)), CF(total) (pixel area of both IS and extrasynovial vascular signals/area (IS)) and number of IS (N(IS)) and extrasynovial (N(ES)) vascular signals. Images were stored and independently rated for both CDUS and QUS by two different raters blinded to each other's rating. Results: Demographics of patients were: mean age 48±16.7 years, mean disease duration 24 months (range 4–600), mean DAS28 of 2.98±1.18 and 40% (38/95) had active disease. CDUS findings were: synovial proliferation: grade 1: 27.4%, grade 2: 54.7%, grade 3: 11.6%; vascularity: grade 1: 41.1%, grade 2: 32.6% and grade 3: 9.5%. Summary findings of QUS were: CF(IS): 8.6±10.63 (median 4.4), CF(total): 9.9±11 (median 5.2), median N(IS): 3 (0–26) and mean N(ES): 1.2 (0–19). Cohen's kappa for synovial proliferation was 0.402 (p<0.001) and vascularity was 0.605 (p<0.001). Intraclass correlation (ICC(1, 2)) for CF(IS) was 0.996 (95% confidence interval (CI): 0.994–0.997) and ICC(1, 2) for CF(total) was 0.995 (95% CI: 0.993–0.997). CF(IS) was correlated with SJC (r=0.22, p=0.029), TJC (r=0.39, p<0.001), PGA (r=0.5, p<0.001), EGA (r=0.583, p<0.001) and DAS28 (r=0.47, p<0.001); correlations for CF (total) were: SJC (r=0.25, p=0.013), TJC (r=0.41, p<0.001), PGA (r=0.525, p<0.001), EGA (r=0.515, p<0.001) and DAS28 (r=0.5, p<0.001). Significant correlations were also observed for N(IS) with SJC (r=0.282, p=0.006), TJC (r=0.411, p<0.001), PGA (r=0.48, p<0.001), EGA (r=0.514, p<0.001) and DAS28 (r=0.467, p<0.001). Spearman rank correlations of CDUS vascularity were: SJC (r=0.26, p=0.01), TJC (r=0.292, p=0.004), PGA (r=0.26, p=0.012), EGA (r=0.168, p=0.103) and DAS28 (r=0.275, p=0.007). Spearman rank correlations of CF(IS), CF(total) and N(IS) with CDUS vascularity were 0.828, 0.864 and 0.689 respectively (p<0.001). Cut-off values for CF(IS), CF(total) and N(IS) for distinguishing active RA from RA in remission were 4.78 (AUC: 0.82, 95% CI: 0.73–0.9), 5.75 (AUC: 0.89, 95% CI: 0.69–0.88) and 2.5 (AUC: 0.77, 95% CI: 0.68–0.86) respectively. There were 40 patients with CDUS vascularity ≥2 among which 62.5% (25/40) had active disease. In this group only CF(total) >5.75 could distinguish between patients with active disease from disease in remission (100% (25/25) vs., 80% (12/25), p=0.046). Conclusions: CF(IS) and CF(total) had excellent inter-rater reliability and construct validity. Simple quantitative cutoff values could distinguish between active RA from remission. Disclosure of Interest: None declared